(untitled) (Medical Forum Monthly, 2024)
Objective: To compare the results of Endoscopic DCR with silicon intubation and without silicon intubation. Study Design: Cross sectional study Place and Duration of Study: This study was conducted at the Lyari General Hospital Karachi from June 2011 to May 2014. Materials and Methods: Total 100 patients were included in this study. They were divided into 2 groups. Group A consisted 50 (50%) patients operated for EDCR with silicon intubation and 50 (50%) included Group B patients underwent EDCR without use of silicon. Age difference was also seen among both groups. Patients aged 15 to 30 years were in majority. Results: This age group included 40(40%) patients. 29(29%) patients aged from 31-40 years. 21(21%) had age of 41-50 years. 10(10%) patients were of age between 51 to 70 years. Female ratio dominated over male in gender incidence. 60 (60%) females and 40 (40%) males were sufferrers. Conclusion: EDCR with Silicon Intubation was seen to be better as compared to the procedure without intubation as the former had least complication rate and higher success rate as compared to the latter.